Komparasi Protokol Komunikasi pada Sistem Produksi Siber-Fisik berbasis IEC 61499 - Aryandaru, Rico; Wardana, Awang Noor Indra; Arif, Agus (Faculty of Engineering, Universitas Brawijaya, 2020)
The change in the concept of an automation pyramid into an automation cloud in a cyber-physical production system makes data communication no longer stratified but can be done directly between devices. Based on IEC 61499, which defines the function blocks for building such communications, communication protocols can be run on various devices. Several communication protocols that can fulfill these requirements are OPC-UA, FBDK / IP, and MQTT. The research was conducted by comparing the three communication protocols for latency parameters and their jitters. The test method used to compare latency parameters is the variance analysis test and the Tukey test. The jitter value of the protocols are compared to the standard deviation parameter. The test results showed that the MQTT communication protocol had a faster latency value, with a 95% confidence level. The standard deviation of the variation value for OPC-UA, FBDK / IP, and MQTT showed the jitter value of 0.72 seconds, 0.35 seconds, and 0.64 seconds. Comparing the three communication protocols' standard deviation values showed that the FBDK / IP communication protocol has significantly less jitter than the OPC-UA and MQTT communication protocols.